The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1007/s00125-016-3992-6
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily delayed-release metformin lowers plasma glucose and enhances fasting and postprandial GLP-1 and PYY: results from two randomised trials

Abstract: Aims/hypothesisDelayed-release metformin (Metformin DR) was developed to maximise gut-based mechanisms of metformin action by targeting the drug to the ileum. Metformin DR was evaluated in two studies. Study 1 compared the bioavailability and effects on circulating glucose and gut hormones (glucagon-like peptide-1, peptide YY) of Metformin DR dosed twice-daily to twice-daily immediate-release metformin (Metformin IR). Study 2 compared the bioavailability and glycaemic effects of Metformin DR dosages of 1,000 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 42 publications
(45 reference statements)
0
76
0
2
Order By: Relevance
“…Pharmacokinetic and dose-ranging studies have demonstrated that MetDR has a glucose-lowering efficacy comparable with that of extended- release metformin but with a 40% increase in potency, thus allowing for lower doses of MetDR to be used [27]. In line with this, two randomised trials demonstrated that MetDR resulted in glucose-lowering effects comparable with immediate-release metformin, despite significantly lower systemic exposure [26]. Large-scale Phase III clinical trials are now needed, as well as studies in individuals with renal impairment, to fully elucidate the efficacy and safety of MetDR.…”
Section: Current Prevention and Treatment Strategies For Hyperglycaemmentioning
confidence: 99%
“…Pharmacokinetic and dose-ranging studies have demonstrated that MetDR has a glucose-lowering efficacy comparable with that of extended- release metformin but with a 40% increase in potency, thus allowing for lower doses of MetDR to be used [27]. In line with this, two randomised trials demonstrated that MetDR resulted in glucose-lowering effects comparable with immediate-release metformin, despite significantly lower systemic exposure [26]. Large-scale Phase III clinical trials are now needed, as well as studies in individuals with renal impairment, to fully elucidate the efficacy and safety of MetDR.…”
Section: Current Prevention and Treatment Strategies For Hyperglycaemmentioning
confidence: 99%
“…Recent evidence suggests that gut stimulation of GLP-1 secretion by the L cells is an important mechanism via which metformin suppresses hepatic glucose production (43,44). …”
Section: Biological Actions Of Glp-1 Rasmentioning
confidence: 99%
“…[17] A novel delayed-release preparation of metformin has been shown to improve glycemic control to a similar extent to immediate-release metformin, but with less systemic exposure. [18,19]. However, whether delayed release metformin will provide better management of T2D remains an open question.…”
Section: Mode Of Action Revisitedmentioning
confidence: 99%